The Power of Letters: John Van Nest Talmage, the Creation of Amoy Romanization, Translation Practice, and Its Social Impact - XIE, Jiapeng (Journal of Research for Christianity in China (JRCC), 2026)
This article uses John Van Nest Talmage, a nineteenth-century Reformed Church missionary in Amoy (Xiamen), as a case study to show how dialect Bible work moved from speech to script, from texts to classrooms and circulation, and thereby shaped society. Drawing on archives, mission reports, letters, and early romanized materials, it traces the formation of Amoy Romanization (Pe̍h-ōe-jī), Talmage’s translation practices, and the social impact generated through the circulation of Bible portions, hymns, primers, dictionaries, and other related texts. Findings: a low-barrier writing system, sustained text supply, and the work of women’s classes and local teachers rapidly lifted grassroots literacy—women first—and extended reading beyond religious use. This shift helped congregations move from an externally driven model to locally led self-reliance. The resulting corpus, together with E-mng-im ê Jī-tián (Dictionary of the Xiamen Dialect), informed later Chinese romanization efforts and supported Fujian dialectal studies. The Talmage case clarifies how dialect translation fueled local social change and cultural renewal.
Keywords: John Van Nest Talmage, Romanized Amoy Colloquial, Translation Practice, Social Impact